Experimental investigation of emissions and flame stability for steel and metal fiber cylindrical premixed burners. Issue 3 (4th March 2019) - Schiro, Fabio; Stoppato, Anna
ABSTRACT: In the market of gas-fired devices, the share of condensing premixed boilers has strongly increased over the last years, since these devices will be the leading technology in the near future. Despite this, premixed burner design is currently mostly driven by trial and error methodology. Scientific research on burner concepts is active on theoretical, numerical, and experimental points of view, but there is a lack in appliance-oriented research. In the present study, the authors experimentally investigate the performance of cylindrical premixed burners coupled to a very common commercial premixed boiler setup, with special attention to the metal fiber application: the aim is to generate knowledge on applied premixed combustion, in order to assist future appliance-oriented burner design processes. A test protocol has been defined. Emission and flame stability characteristics have been identified for steel and fiber burners. The metal fiber contribution to the combustion behavior has been highlighted.